Advance electrochemical oxidation of fipronil contaminated wastewater by graphite anodes and sorbent nano hydroxyapatite. Issue 7 (3rd April 2019) - Thangamani, Ramya; Muthusamy, Muthukumar; Manickam Periyaraman, Premkumar; Thanarasu, Amudha; Devaraj, Thiruselvi; Dhanasekaran, Anuradha; Sivanesan, Subramanian
ABSTRACT: Degradation of C12 H4 Cl2 F6 N4 OS phenylpyrazole insecticide (Fipronil) by advance electrochemical oxidation in aqueous water solution was studied. The process efficiency was figured based on the COD, chloride, and fluoride reduction from fipronil. Further, we tried to highlight the importance of nano-hydroxyapatite (n-Hap) as a cost-effective nano sorbent for removal of fluoride from fipronil. From the advance electrochemical oxidation experiment, it was found that the COD removal was 79%, chloride 52%, and fluoride 80%. The intermediate of fipronil compounds was examined by GC-MS. The final results conclude that advance electrochemical oxidation process was effective for removal of fipronil synthetic wastewater.